Intelligent Decision Making Technique for Marketing Using Hypothetical Database and Fuzzy Multi-Criteria Method - A. Fareed,; Ansar A. Khan,; B. Mahmood ,; H. Shamsul, (Journal of Basic & Applied Sciences, 2013)
Marketing organizations use databases to locate potential customers and to generate sales lead. A number of software systems have been playing a key role in supporting the decision making activities in recent years but common problem in all that they cannot handle fuzzy data appropriately for "what-if" analysis. This paper proposes intelligent scenarios analysis system framework for marketing decision support which deals with crisp and fuzzy data like linguistic variable. Applying new approach "Hypothetical Database" for derived data that permits decision manager to manage views according to the need of organization and/or market environment. View in Hypothetical Database provides versatility in "What-If" analysis by using versions of "What-If" database and reduce data redundancy and data storage in updating. Using Fuzzy database will help to handle imprecise and uncertain information like "Linguistic variable" in a more human oriented process. Finally, the projected scenarios selected by decision manager will be aligned in a hierarchy according to the distance from "Ideal Vector" by using Fuzzy Multi-Criteria Decision Making method.